PENGARUH PENGGUNAAN TEKNOLOGI PERTANIAN TERHADAP PENDAPATAN DAN PELUANG KERJA BURUH TANI ( Studi Kasus Masyarakat Desa Balongpanggang Kecamatan Balongpanggang Kabupaten Gresik ) - administrator, administrator; Nurfauzia, Ananda Istiqomah; Syahrial, Ramon (Fakultas Pertanian Universitas Wijaya Putra, 2023)
This study discusses the about influence of agricultural equipment technology on employmentopportunities and farm laborers' income in Balongpanggang, Balongpanggang sub-district,Gresik district. The purpose of this research is to find out how the technology of agriculturalequipment affects the employment opportunities and income of farm worker. The existence ofagricultural equipment technology has negative and positive impacts in Balongpanggangvillage, the conclusion from this study is that the negative effect means that the decreasingAgricultural Equipment Technology will affect the increase in Job Opportunities for farmlaborers and for this positive influence it means that the increasing Agricultural EquipmentTechnology will affect This increase in income is because the technology of agriculturalequipment is considered to save working time and costs in land management. But on the otherhand, the presence of agricultural equipment technology has also shifted the work of farmlaborers who initially used traditional tools. The type of research used is quantitative researchwith a population of farmhands in the village of Balongpanggang and using the saturationtheory formula, namely with 23 respondents and all of them will be sampled. The method usedto test this research is to test the validity, reliability test, t test , classic assumption test, pearsonbivariate correlation test and simple regression analysis. The analytical tool in this study usesSPSS version 20